The efficiency of wages, profit sharing, and stock. Issue 3 (9th December 2019) - Weltmann, Dan
Abstract : Purpose: The purpose of this paper is to examine which forms of compensation are more efficient at affecting employee attitudes, thus extending efficiency wage theory from wage-based compensation to profit sharing and stock-based compensation. Design/methodology/approach: Three models of efficiency wage theory were tested: shirking, turnover and gift exchange. The effects of those three modes of compensation (wages, profit sharing and stock) were contrasted for the three models of efficiency wage theory. Findings: The findings were that raising wages is the most efficient form of compensation in the turnover and shirking models, while in the gift exchange model profit sharing and stock-based compensation may function like efficiency wages. Originality/value: This is the first study of this particular issue.